(untitled) (Revista cientifica In Vestigium Ire, 2019)
Colombia is undergoing a process of convergence to the international norm starting from Law 1314, for this reason the General Accounting Office of the Nation, as a regulating entity of public accounting, created three scenarios for this convergence process. However, this represents a challenge for the entities and the accountants because, due to the novelty of the process, all the findings found have not yet been documented for Group 3, which are entities of the central government. This research aims to account for the main findings that can be found in a public entity, based on the follow-up to the implementation of the rule according to resolution 533 of 2015 in the municipality of Buenavista, Boyacá, and to issue operational policies that will guide the process to avoid repeating those errors in the municipality’s accounting, applying a case study methodology, with a descriptive approach, where the instruments for gathering information were observation, interviews with public officials, matrices designedaccording to the norm established for public entities, analysis of documents based on appraisals carried out with external firms and review of inventories. The main result obtained was the state of financial situation of the municipality with initial balances, evidencing an impact of 93% on the patrimony as a result of the identification, measurement and disclosure of the property, plant and equipment.